PSA density and prostate cancer detection - Armean Saema (2018)
Objective: To evaluate the diagnostic value of prostate-specific antigen density (PSAD) and the appropriate cutoff for the detection of prostate cancer. Material and Method: Between January 2008 and March 2011, 292 men with PSA levels between 4 and 10 ng/mL underwent Transrectal Ultrasonography (TRUS) with prostate biopsy. The diagnostic value of PSA levels and PSAD were compared using receiver operating characteristic curves. Results: Prostate cancer was diagnosed in 64 (22%) of the 292 men who had PSA levels 4 to 10 ng/mL. The mean PSA level was 6.96 ng/mL. The mean age was 66 years. The area under the curve (AUC) of PSA and PSAD were 0.475 and 0.665, respectively. The sensitivity and specificity of PSAD at cutoff of 0.15 was 78% and 43%, respectively. Conclusion: PSAD was a better discriminator of prostate cancer than PSA for PSA levels less than 10 ng/ml. Our data suggested that a different PSAD cutoff than previously recommended need to be defined for Thai people.